Disruption of Immune Homeostasis in Human Dendritic Cells via Regulation of Autophagy and Apoptosis by Porphyromonas gingivalis - Meghil, Mohamed M.; Tawfik, Omnia K.; Elashiry, Mahmoud; Rajendran, Mythilypriya; Arce, Roger M.; Fulton, David J.; Schoenlein, Patricia V.; Cutler, Christopher W. (Frontiers in Immunology, 2019)
As fundamental processes of immune homeostasis, autophagy and apoptosis must be maintained to mitigate risk of chronic inflammation and autoimmune diseases. Periodontitis is a chronic inflammatory disease characterized by oral microbial dysbiosis, and dysregulation of dendritic cell (DC) and T cell responses. The aim of this study was to elucidate the underlying mechanisms by which the oral microbe Porphyromonas gingivalis (P. gingivalis) manipulates dendritic cell (DC) signaling to perturb both autophagy and apoptosis. Using a combination of Western blotting, flow cytometry, qRT-PCR and immunofluorescence analysis, we show a pivotal role for the minor (Mfa1) fimbriae of P. gingivalis in nuclear/cytoplasmic shuttling of Akt and FOXO1 in human monocyte-derived DCs. Mfa1-induced Akt nuclear localization and activation ultimately induced mTOR. Activation of the Akt/mTOR axis downregulated intracellular LC3II, also known as Atg8, required for autophagosome formation and maturation. Use of allosteric panAkt inhibitor MK2206 and mTOR inhibitor rapamycin confirmed the role of Akt/mTOR signaling in autophagy inhibition by P. gingivalis in DCs. Interestingly, this pathway was also linked to induction of the anti-apoptotic protein BCL2, decreased caspase-3 cleavage and decreased expression of pro-apoptotic proteins Bax and Bim, thus promoting longevity of host DCs. Addition of ABT-199 peptide to disrupt the interaction of antiapoptotic BCL2 and its proapoptotic partners BAK/BAX restored apoptotic death to P. gingivalis-infected DC cells. In summary, we have identified the underlying mechanism by which P. gingivalis promotes its own survival and that of its host DCs.